Analisis Perbandingan Metode Fuzzy Mamdani, Sugeno dan Tsukamoto Dalam Menentukan Harga Smartphone Bekas - Ilham Farhandhany; Galuh Surya Permana; Muhammad Syam Noverick; Muhammad Dzulkifli Hidayah Ramadhan; Perani Rosyani (Buletin Ilmiah Ilmu Komputer dan Multimedia, 2023)
The sales of used smartphones or devices increase with the purchase of new smartphones or devices because most people sell their old smartphones or devices before buying new ones with advanced features. Ratings are still used for selling used smartphones or electronic devices, resulting in unexpected outcomes. To overcome this problem, a system is needed to accurately determine the selling price of smartphones or electronic devices. By comparing different journals and using Fuzzy Inference System (FIS); B. Fuzzy Sugeno, Fuzzy Mamdani, and Fuzzy Tsukamoto methods, it aims to assist those who want to buy orsell smartphones with more detailed information about the terms and conditions of the smartphones being bought orsold. From the comparative analysis of fourjournals using different methods, it is concluded that theMamdani method is the best method for determining the price of used smartphones. Moreover, both journalsthat use the Mamdani method have higher accuracy scores, achieving 100% validity compared to the Sugeno and Tsukamoto methods. The purpose of this comparison is to find a good way to determine the price of used smartphones.